2018
DOI: 10.2139/ssrn.3161323
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity Risk and Yield Spreads of Green Bonds

Abstract: This study analyses how liquidity risk affects bonds' yield spreads after controlling for credit risk, bond-specific characteristics and macroeconomic variables. Using two liquidity estimates, LOT liquidity and the bid-ask spread, we find that, in particular, the LOT liquidity measure has explanatory power for the yield spread of green bonds. Overall, however, the impact of LOT decreases over time, implying that, nowadays liquidity risk is negligible for green bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
(33 reference statements)
1
8
0
1
Order By: Relevance
“…To analyze further differences in characteristics between green and brown bonds from private versus institutional issuers, we re-estimated the liquidity and variance specifications in Equations (2) and (3) for the two different groups. Results on liquidity differences are shown in Table 9.…”
Section: The Institutional-private Issuer Breakdownmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze further differences in characteristics between green and brown bonds from private versus institutional issuers, we re-estimated the liquidity and variance specifications in Equations (2) and (3) for the two different groups. Results on liquidity differences are shown in Table 9.…”
Section: The Institutional-private Issuer Breakdownmentioning
confidence: 99%
“…Zerbib [1] showed that there is a mostly negative green bond premium, which is especially high in some market segments, claiming that the rating and the amount issued are the main drivers of the premium. Wulandari et al [2] analyzed how liquidity risk affects the yield spread between a couple of matched green and brown bonds, arguing that liquidity risk is negligible for green bonds. Reboredo [3] found that green bond returns are strictly correlated with corporate and treasury bond returns, whereas they weakly co-move with stocks and energy commodities.…”
Section: Introductionmentioning
confidence: 99%
“…Their results, through the period 2014-2017, reflect that green and climate-aligned muni indices present compound annual growth rates of 4.5%, compared with 3% for the S&P Investment Grade Municipal index, showing the outperformance of such green and climate-aligned financing tools. Wulandari et al (2018) focus their work on the Green Bond issuer side by assessing the relation between liquidity risk and yield spread evolution. The findings show that both the "LOT" liquidity and the bid-ask indicators are positively related to the yield spread.…”
Section: Green Bond Marketmentioning
confidence: 99%
“…Understanding the supply‐side dynamics is equally, if not more, important than demand‐side in shaping green bonds market for a greener economy (Caldecott, ; Mathews & Kidney, ). However, although there are some studies on green bond market drivers, particularly relating to demand (e.g., OECD, ; Wood & Grace, ; Wulandari, Schäfer, Andreas, & Sun, ; Zerbib, ), studies concerning supply‐side remain limited. In particular, to the best of our knowledge, no empirical study yet provides an understanding of the effects of green bonds supply on the market.…”
Section: Introductionmentioning
confidence: 99%